2018
DOI: 10.1021/acssuschemeng.8b00009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Corynebacterium glutamicum for the High-Level Production of Cadaverine That Can Be Used for the Synthesis of Biopolyamide 510

Abstract: Fermentative production of cadaverine from renewable resources may support a sustainable biorefinery process to produce carbon-neutral nylons such as biopolyamide 510 (PA510). Cost-competitive production of cadaverine is a key factor in the successful commercialization of PA510. In this study, an integrated biological and chemical process involving cadaverine biosynthesis, purification, and its polymerization with sebacic acid was developed to produce bio-PA510. To stably express ldcC from Escherichia coli in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
140
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(151 citation statements)
references
References 47 publications
9
140
2
Order By: Relevance
“…Because lysine decarboxylase is a key enzyme for cadaverine production, codon optimization, chromosomal integration ( bioD for ATP‐dependent dethiobiotin synthetase; lysE for l ‐lysine exporter), and expression under strong promoters (P tuf and P H30 ) greatly affect the final titer of cadaverine produced by recombinant C. glutamicum (Fig. ) . When ldcC from E. coli W3110 was codon‐optimized for C. glutamicum and integrated into the bioD locus for the chromosomal‐based expression of LDC, the final titer of cadaverine was 88 g L −1 from fed‐batch fermentation.…”
Section: Production Of Polyamide Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Because lysine decarboxylase is a key enzyme for cadaverine production, codon optimization, chromosomal integration ( bioD for ATP‐dependent dethiobiotin synthetase; lysE for l ‐lysine exporter), and expression under strong promoters (P tuf and P H30 ) greatly affect the final titer of cadaverine produced by recombinant C. glutamicum (Fig. ) . When ldcC from E. coli W3110 was codon‐optimized for C. glutamicum and integrated into the bioD locus for the chromosomal‐based expression of LDC, the final titer of cadaverine was 88 g L −1 from fed‐batch fermentation.…”
Section: Production Of Polyamide Monomersmentioning
confidence: 99%
“…To improve the production of cadaverine, industrial l ‐lysine‐overproducing C. glutamicum PKC was used as a host for the chromosomal integration of E. coli ldcC under the control of a strong H30 promoter into lysE locus. This enabled the stable expression of LDC and deletion of l ‐lysine export activity, which led to increased cadaverine production (104 g L −1 ) . To improve the export of cadaverine, the overexpression of a putative putrescine exporter gene ( cgmA) enhanced the extracellular cadaverine concentration .…”
Section: Production Of Polyamide Monomersmentioning
confidence: 99%
“…21 Kim et al reported that ldcC from E. coli was integrated into the chromosome of the C. glutamicum PKC strain, which was expressed through a strong synthetic promoter H30, and the engineered strain produced a concentration of 103.78 g L -1 cadaverine from glucose by fed-batch culture. 22 To our understanding, these research results about the bioproduction of cadaverine suggest their suitability for scaling-up to industrial production.…”
Section: Introductionmentioning
confidence: 92%
“…Polyamides (PA) are an essential polymer and widely used in engineering plastics, sportswear, sutures and catheters, owing to the excellent mechanical and thermal strength (Park et al, 2014;Jiang and Loos, 2016;Kim et al, 2018). Polyamides are mostly produced from chemicals extracted from fossil fuels (6.6 million tons per year), which contributes to the greenhouse effect and serious environmental pollution (Hong et al, 2004;Kind et al, 2011).…”
Section: Introductionmentioning
confidence: 99%